It's the occupation, stupid! Explaining candidates' success in low-information elections - Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
Do voters use ballot paper information on the personal characteristics of political candidates as cues in low-information elections? Using a unique dataset containing 4423 political candidates from recent elections in Germany, we show that candidates' occupations do play an important role in their electoral success. The occupational impact is far greater than gender or doctoral degree effects for a large number of occupations. We discuss three possible explanations for these 'occupational effects': (a) an occupation's public reputation, (b) the extent to which individuals carrying out certain occupations are known within their communities, and (c) occupation specific competence related to issues relevant for local politics. Looking at polls on the reputation/ prestige of certain jobs, we find a strong correlation between an occupation's reputation and the electoral success of a candidate carrying out this occupation. Therefore, voters appear to use occupational reputation as a cue in low-information elections.
Keywords: D72; D7; 330; political economy; low-information elections; informational shortcuts; occupational reputation